(untitled) (Książnica Śląska, 2025)
The article presents the results of research on architecture dedicated to the new headquarters of the Silesian Library in Katowice. Efforts undertaken for over five decades in the second half of the 20th century to create a modern building for the Library resulted in a collection of architectural designs developed by the most distinguished designers for the region, including Julian Duchowicz, Zygmunt Majerski, Tadeusz Łobos, Jurand Jarecki, Stanisław Kwaśniewicz and Marek Gierlotka. The article complements and organizes knowledge about these projects and conducts their synthetic stylistic analysis.